Diet and Oviposition Deprivation Effects on Survivorship, Gonotrophic Dissociation, and Mortality of Anopheles gambiae s.s. - Paulo S. Chisulumi; Bahati Nampelah; Revocatus Yohana; Anitha Philbert; Eliningaya J. Kweka (Journal of Parasitology Research)
Diet quality is of paramount importance for egg batch size, longevity, and mortality of vector mosquitoes. Oviposition site presence and absence assumed to be dry season means a lot to the survivorship and mortality of most anthropophilic malaria vectors in sub-Saharan Africa. This study has assessed the effect of different diets and oviposition-site deprivation (OSD) on survivorship, longevity, and mortality of An. gambiae s.s. To determine the effect of diet and OSD on mortality, gonotrophic dissociation rates, longevity, and survivorship, six treatments were employed: Blood Fed with Oviposition (BFO), Blood Fed without oviposition (BF), Blood and Sugar Fed with Oviposition (BSFO), Blood and Sugar Fed without oviposition (BSF), Sugar Fed with Oviposition (SFO), and Sugar Fed without oviposition (SF). Mortality and gonotrophic dissociation were monitored daily. This study found that female mosquitoes offered blood meals with sugar solution and oviposition deprivation survived longer than those deprived of oviposition deprivation. Similarly, female mosquitoes fed on blood and provided with oviposition deprivation lived longer than those without oviposition deprivation. The gonotrophic dissociation rates were found to be lower in groups provided with oviposition deprivation. Our results show that OSD has a direct impact on the survivorship, gonotrophic dissociation rate, and longevity of the malaria anthropophilic vector, An. gambiae s.s., regardless of the diet.